Developing a Conceptual Framework for Innovative Behaviour in Healthcare Organization - Wan Abd Aziz, Wan Mohd Amin; Lina Iziana, Ghazali (2018)
In recent years, healthcare face challenges to be more responsive to the increased demands of public for better quality of care. In order to ensure public received with good healthcare services, the most important employees are nursing professionals who are responsible to emphasise on delivering quality and efficient. Based on literature, innovation can become a good solution to increase patient care quality. Healthcare depend on their nurses to continuous innovate their ways of working that actually improve nursing practice. Previous study found that leadership is important antecedent of innovative behaviour. This study is an attempt to examine transformational leadership on innovative behaviour among nurses. The structural equation modelling has been proposed and will be used to test the impact of transformational leadership towards innovative behaviour.